WORK TRANSFORMATION FROM FISHERMAN TO HOMESTAY TOURISM ENTREPRENEUR: A STUDY IN MANTANANI ISLAND KOTA BELUD, SABAH, EAST MALAYSIA (Jurnal Kemanusiaan, 2017)
Most of the residents in Mantanani Island are from the Bajau Ubian ethnic group, where they work as a fisherman in the coast. The total population of this group here is 800 people. However, the future of the community and its fishing activities, which were bright once, is now presently unhappy due to illegal practices like fish-bombing that has caused serious depletion of the coral reefs, aquatic life and marine resources around the Mantanani Island. The current situation is creating a worse phenomenon, where the fisherman can only catch a small quantity of fish and fish resources not as much as before. In addition, deep sea fishing activities have caused a decrease in fish caught by local fisherman of Mantanani Island. As a result, the monthly income falls below the poverty line in that area. The Mantanani Island community needs a transformation for survival and a variety of alternative employment and economic activities to sustain their livelihood such as homestay entrepreneurship. This is because Mantanani Island has beautiful natural scenery and nowadays has become a primary international tourists’ top destination, particularly for those who are from the regions such as Europe, Japan, Korea, China, Australia and United States. The survey method, a quantitative research approach was used in this study besides other methods such as field observation and secondary data. The findings indicated that the Mantanani Island community is interested to accept social transformation but they still need support from the government, private sectors and NGO’s to successfully overcome obstacles and limitations.